2020
DOI: 10.1111/mcn.12998
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits and sleep patterns of adolescents with depression symptoms in Mumbai, India

Abstract: Adolescents with depression engage in unhealthy eating habits and irregular sleep patterns and are often at an increased risk for weight‐related problems. Improvement in these lifestyle behaviours may help to prevent depression, but knowledge about the associations between depression, sleep, eating habits and body weight among adolescents in India is limited. This cross‐sectional study investigated the prevalence of depression and its association with sleep patterns, eating habits and body weight status among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 62 publications
5
30
0
Order By: Relevance
“…Alterations in the sleep-wake cycles due to delay in school start time [ 38 ], increased vulnerability to anxiety and depression symptoms due to COVID-related fear and social isolation [ 19 ], and limited peer interactions to handle academic frustrations and loneliness [ 39 ] seem to have further worsened the already pervasive sleep problems and mental health crisis in adolescents globally and India. Similar to our findings, other studies had shown the prevalence of sleep and depression to be higher among females and older adolescents [ 38 , 40 ], indicating that this group might require particular attention during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Alterations in the sleep-wake cycles due to delay in school start time [ 38 ], increased vulnerability to anxiety and depression symptoms due to COVID-related fear and social isolation [ 19 ], and limited peer interactions to handle academic frustrations and loneliness [ 39 ] seem to have further worsened the already pervasive sleep problems and mental health crisis in adolescents globally and India. Similar to our findings, other studies had shown the prevalence of sleep and depression to be higher among females and older adolescents [ 38 , 40 ], indicating that this group might require particular attention during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, future work should be focused on laying down unified criteria to facilitate the comparison of results. We also found that the prevalence of depression was also higher than previously reported in the United States (8.7–11.3%) ( 52 ) and lower than that in Ethiopia (28%) ( 53 ) and India (25%) ( 54 ). Research shows that adolescents in Confucian countries in Asia have higher levels of depression than those in European countries ( 55 ), which may be explained by a higher prevalence of abuse.…”
Section: Discussionsupporting
confidence: 56%
“…Evidence suggests that depression in adolescents may be associated with risky behaviors such as insufficient levels of physical activity [ 11 , 12 , 13 , 14 ], psychoactive substance use [ 15 ], unhealthy eating habits [ 16 , 17 , 18 ], and risky sexual behavior [ 19 , 20 ]. Experts argue that there may be a positive relationship between physical activity and brain health in adolescents, which involves both cognitive function and mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%